2021
DOI: 10.1371/journal.pone.0247204
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards COVID-19 among health professionals in Ethiopia: A systematic review and meta-analysis

Abstract: Background The World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) a global pandemic on 11th March, 2020. In Ethiopia, more than 90,490 and 1,300 confirmed cases and deaths were reported by the Federal Ministry of Health at the time of writing up this project. As health care providers are frontline workers managing the COVID-19 pandemic, this systematic review and meta-analysis aimed to assess the pooled level of knowledge, attitude, and practice towards COVID-19 among health professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 19 publications
(17 reference statements)
5
31
4
Order By: Relevance
“…COVID-19 with multiple challenges is greatly affecting all systems of the country of Ethiopia and it is alarming for the gov’t, stakeholders, and every citizen of the country to combat the pandemic [ 17 1 ]. In Ethiopia, overall health professional’s knowledge, attitude, and practice to COVID-19 are poor [ 19 ]. Also, low-level preparedness to prevent the pandemic with limited personal protective equipment supplies contributes to the rapid spread of COVID-19 in Ethiopia [ 17 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 with multiple challenges is greatly affecting all systems of the country of Ethiopia and it is alarming for the gov’t, stakeholders, and every citizen of the country to combat the pandemic [ 17 1 ]. In Ethiopia, overall health professional’s knowledge, attitude, and practice to COVID-19 are poor [ 19 ]. Also, low-level preparedness to prevent the pandemic with limited personal protective equipment supplies contributes to the rapid spread of COVID-19 in Ethiopia [ 17 – 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, overall health professional’s knowledge, attitude, and practice to COVID-19 are poor [ 19 ]. Also, low-level preparedness to prevent the pandemic with limited personal protective equipment supplies contributes to the rapid spread of COVID-19 in Ethiopia [ 17 – 19 ]. The preparedness level to combat the pandemic in the study area was low and daily reports of COVID-19 positive patients are rapidly increasing [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A range of reports has shown that up to 40% of the general population had unfavorable views about potential COVID-19 vaccines ( Bhartiya et al, 2021 ; Lake et al, 2021 ; Verger et al, 2021 ). One of the principal factors behind these attitudes seems to be a concern that the new vaccines will not be safe ( Lin et al, 2020 ; Verger et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the most efficient way of controlling the spread of the virus is to protect oneself from being exposed to COVID-19, it is very important to vaccinate the community’s vulnerable group, such as immigrants ( Acharya et al, 2020 ; Mannan and Farhana, 2020 ; Lake et al, 2021 ). A study found that only 54% of the respondents said that they intended to have the vaccination ( Lin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have assessed KAP towards COVID-19 among HCWs in Africa. Whereas some of these studies have reported adequate COVID-19-related KAP among HCWs [ 29 , 30 ], others have found significant gaps [ 31 , 32 ]. In the current study, we assessed KAP towards COVID-19 among HCWs in Uganda with the aim of informing national COVID-19 prevention and control efforts.…”
Section: Introductionmentioning
confidence: 99%